Historical Land Use and Land Cover Change of the Lake Tempe Region: A Multi-source Data Landscape Reconstruction - Syahruddin Mansyur; Nur Ihsan Djindar; Wasita Wasita; Imam Hindarto; Nani Somba; Hasrianti Hasrianti; Moh. Ali Fadillah; Hamka Naping; Sofyan Setia Budi (Forest and Society)
Lake Tempe, situated in the Wajo Regency, is an ancient lake in Indonesia that plays a crucial role in the socio-historical evolution of Southern Sulawesi. The Lontara manuscript, a significant source of regional history, highlights Lake Tempe as a vital resource for adjacent communities. Contemporary narratives of Lake Tempe, however, are overshadowed by recurrent flooding attributed to accelerated sedimentation leading to lake shallowing, which impedes its capacity to manage the inflow from tributary rivers. This study aims to offer a historical perspective by reconstructing the landscape and detailing the evolution of land use and land cover (LU/LC) in the Lake Tempe region, thus enhancing our understanding of the lake's current conditions. We compiled an array of historical and archaeological data, including manuscripts, archival maps, and satellite imagery, spanning the 13th to 20th centuries. Our approach involves historical LU/LC modeling to provide an intricate depiction of the landscape evolution in the Lake Tempe area. Moreover, we presented modeled projections of LU/LC alterations over approximately 86 years (1930-2016). The analysis reveals that pre-20th century landscape dynamics in the region were influenced by several factors: demographic shifts due to local migration, interplay among local elites over natural resource control, and integration into global trade networks from the 13th century onwards. These elements collectively spurred deforestation during periods of agricultural expansion. Starting in the early 20th century, the agricultural development policies of both the Dutch Colonial and the Republic of Indonesia's governments further accelerated land conversion for distinct agricultural purposes. This historical narrative underscores the fact that centuries of anthropogenic activity have been central to the hydrometeorological challenges faced throughout the Lake Tempe region.